2020
DOI: 10.7759/cureus.10492
|View full text |Cite
|
Sign up to set email alerts
|

Post-Extubation Stridor Complicating COVID-19-Associated Acute Respiratory Distress Syndrome: A Case Series

Abstract: Post-extubation stridor is a known complication of mechanical ventilation that affects a substantial number of all critical care patients and leads to increased morbidity and mortality. Common risk factors for the development of post-extubation stridor include female gender, older age, and prolonged length of mechanical ventilation. There may be an increased incidence of post-extubation stridor in patients who require mechanical ventilation to manage the respiratory complications of COVID-19. In this case seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In a recent laryngological case series [ 24 ], several COVID-19-related upper airway complications, including vocal fold immobility, granulation tissue formation, posterior glottic and subglottic stenosis, and posterior glottic diastasis have been associated with prolonged intubation in prone position and larger (>7.5) caliber orotracheal tubes. High incidence of post-extubation stridor and laryngeal injury among patients who underwent endotracheal intubation and tracheostomy during the COVID-19 pandemic has also been reported in other case series [ 25 , 26 ]. In a number of case reports, it was highlighted that common post-COVID-19 respiratory symptoms, such as cough and dyspnea after discharge from the hospital, were initially misdiagnosed and later attributed to post-intubation tracheal stenosis [ 27 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In a recent laryngological case series [ 24 ], several COVID-19-related upper airway complications, including vocal fold immobility, granulation tissue formation, posterior glottic and subglottic stenosis, and posterior glottic diastasis have been associated with prolonged intubation in prone position and larger (>7.5) caliber orotracheal tubes. High incidence of post-extubation stridor and laryngeal injury among patients who underwent endotracheal intubation and tracheostomy during the COVID-19 pandemic has also been reported in other case series [ 25 , 26 ]. In a number of case reports, it was highlighted that common post-COVID-19 respiratory symptoms, such as cough and dyspnea after discharge from the hospital, were initially misdiagnosed and later attributed to post-intubation tracheal stenosis [ 27 ].…”
Section: Discussionmentioning
confidence: 54%
“…The true incidence of PITS might be even higher as a number of post-COVID patients may not be referred for dyspnea/tracheal stenosis due to more debilitating COVID-related post-ICU sequelae. Other authors have also observed a similar increase in the incidence of these complications, which could either be attributed to the dramatic increase of intubated patients due to the pandemic or to other factors related to specific patients’ characteristics, to the disease itself, or ultimately to iatrogenic factors related with the hospitalization and the disease management under the current circumstances [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 79%
“…This aligns with initial guidelines supporting avoidance of early tracheostomy in patients with COVID‐19. This has changed with recent evidence showing benefits and safety of early tracheostomy with standardized protocols and personal protective equipment 24–26 . Thus, patients with extended intubation may be unique to hospitalizations in 2020, though many will require long‐term management for laryngotracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…To identify patients at risk of laryngeal edema, airway patency assessment before extubation has been evaluated. Since Miller and Cole evaluated 100 mechanically ventilated patients in 1996, the cuff leak test (CLT) has been widely used because of its noninvasiveness and avoidance of sophisticated equipment 11 15 . The cuff leak volume was defined as the tidal volume difference from before to after endotracheal tube (ETT) cuff deflation.…”
Section: Introductionmentioning
confidence: 99%